2014
DOI: 10.1002/adma.201402847
|View full text |Cite
|
Sign up to set email alerts
|

Edge‐Oriented MoS2 Nanoporous Films as Flexible Electrodes for Hydrogen Evolution Reactions and Supercapacitor Devices

Abstract: A simple method to fabricate edge-oriented MoS2 films with sponge-like morphologies is demonstrated. They are directly fabricated through the reaction of sulfur vapor with anodically formed Mo oxide sponge-like films on flexible Mo substrates. The edge-oriented MoS2 film delivers excellent hydrogen evolution reaction (HER) activity with enhanced kinetics and long-term cycling stability. The material also has superior energy-storage performance when working as a flexible, all-solid-state supercapacitor device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
345
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 569 publications
(362 citation statements)
references
References 17 publications
16
345
0
Order By: Relevance
“…Edge‐oriented MoS 2 thin films have been fabricated by a simple and scalable method as illustrated in Figure 18 384. At first, molybdenum metal is electrochemical anodized forming nanostructured Mo oxide porous thin‐films.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…Edge‐oriented MoS 2 thin films have been fabricated by a simple and scalable method as illustrated in Figure 18 384. At first, molybdenum metal is electrochemical anodized forming nanostructured Mo oxide porous thin‐films.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…The coulombic efficiency in various electrolytes at a current rate of 2 A g À1 was as high as 90-98%. Tour et al 130 reported the fabrication of an edgeoriented MoS 2 thin-film by electrochemical anodization of molybdenum metal followed by sulfur vapor treatment (Fig. 12H-J).…”
Section: Applications In Energy Storage Devicesmentioning
confidence: 99%
“…The high activity mainly comes from the sulfur atoms at the edges of MoS 2 6, 7. Extensive efforts have been dedicated to preparing edge‐rich MoS 2 with ample electrochemically accessible active sites to enhance catalyst activity 8, 9, 10, 11, 12, 13, 14. Currently, the preparation of MoS 2 for hydrogen evolution reaction involves complex and time‐consuming processes such as chemical Li‐intercalation and exfoliation,15, 16 chemical vapor deposition growth,17, 18 and hydrothermal/solvothermal reaction 8, 19, 20, 21, 22.…”
Section: Introductionmentioning
confidence: 99%